Natural history of pulmonary coccidioidomycosis: Further examination of the VA-Armed Forces Database. (27th September 2022) - Shemuel, Joseph; Bays, Derek J; Thompson, George R; Reef, Susan; Snyder, Linda; Freifeld, Alana J; Huppert, Milt; Salkin, David; Wilson, Machelle D; Galgiani, John N
Abstract: There are still many limitations related to the understanding of the natural history of differing forms of coccidioidomycosis (CM), including characterizing the spectrum of pulmonary disease. The historical Veterans Administration-Armed Forces database, recorded primarily before the advent of antifungal therapy, presents an opportunity to characterize the natural history of pulmonary CM. We performed a retrospective cohort study of 342 armed forces service members who were diagnosed with pulmonary CM at VA facilities between 1955 to 1958, followed through 1966, who did not receive antifungal therapy. Patients were grouped by predominant pulmonary finding on chest radiographs. The all-cause mortality was low for all patients (4.6%). Cavities had a median size of 3-3.9 cm (IQR: 2-2.9–4-4.9 cm), with heterogeneous wall thickness and no fluid level, while nodules had a median size of 1-1.19 cm (Interquartile range [IQR] 1-1.9–2-2.9 cm) and sharp borders. The majority of cavities were chronic (85.6%), and just under half were found incidentally. Median complement fixation titers in both the nodular and cavitary groups were negative, with higher titers in the cavitary group overall. This retrospective cohort study of non-disseminated coccidioidomycosis, the largest to date, sheds light on the natural history, serologic markers, and radiologic characteristics of this understudied disease. These findings have implications for the evaluation and management of CM. Lay Summary: Coccidioidomycosis (CM), also known as San Joaquin Valley Fever, causes a variety of symptoms including pneumonia. This historical study investigates CM of the lungs in American soldiers with CM in the 1950s, prior to modern antifungals, to better understand the natural history.